The Dynamics of Sexual Orientation in Gays - Fathul Hidayah (Psikologia : Jurnal Psikologi, 2017)
There is a different group of people with certain sexual orientations inside a community. Sexual orientation is divided into three namely heterosexual, bisexual, and homosexual. In this study, which trying to lift the topic of the dynamics of gay sexual orientation. Gay is a sexual inclination which men are intereted into fellow men. There is one thing that is most important in the dynamics of gay orientation, it is called the formation of sexual orientation identity. The purpose of this study is to know the full picture of the dynamics of sexual orientation on gays. This research uses qualitative research method with the design of case study about the life history type. Three Respondents are involved in this study, 1 person as the main respondent and 2 people as significant others. The results of this study indicate that there were several causes until the respondent becomes gay, when he was a 6 grader, he imitated the blue film he watched, then disappointed because he was betrayed by his female partner, and because of the environment that encouraged him to go deeper into the gay world.